2009
DOI: 10.4103/1658-354x.57878
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane-emergence agitation: Effect of supplementary low-dose oral ketamine premedication in preschool children undergoing dental surgery

Abstract: Background and Objectives:The use of sevoflurane in pediatric anesthesia, which could enable a more rapid emergence and recovery, is complicated by the frequent occurrence of post-anesthesia agitation. This study aims to test the efficacy of adding a low dose of ketamine orally, as a supplement to the midazolam-based oral premedication for reducing sevoflurane-related emergence agitation.Materials and Methods:Ninety-two preschool children, aged between two and six years, with an American Society of Anesthesiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…140 retracted articles out of 180 (77.8%) are still available in full text on respective journal websites, and 15 of these still available articles (10.7%) present no evident watermark clearly indicating the presence of a retraction (Acharya & Mandal, ; Asgary & Eghbal, ; Cuoghi, Sella, & de Mendonça, ; Dionysopoulos, Koliniotou‐Koumpia, Helvatzoglou‐Antoniades, & Kotsanos, ; Ellakwa & El‐Sheikh, ; Gulsahi et al, ; Khattab, El‐Seify, Shaaban, Radojevic, & Jankovic, ; Kurtulmus & Cotert, ; Nayyar, Khan, Bafna, Ahmed, & Chaluvaiah, ; Ni, Lin, Liu, & Xiao, ; Palenik, ; Scotti, Cardelli, Baldissara, & Monaco, ; Sumanth et al, ; Wang et al, ). The abstracts of 157 out of 180 retracted publications (87.2%) are still available on Pubmed, but 8 of these (5.1%) present neither a footnote nor any clear indication of the presence of a retraction notice (Agrawal, Singh, Rashmikant, Singh, & Chand, ; Dumitrescu, Zetu, & Teslaru, ; Ehrlich et al, ; Kumar et al, ; Maté Sánchez de Val et al, ; Rabanal, Bral, & Goldstein, ; Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…140 retracted articles out of 180 (77.8%) are still available in full text on respective journal websites, and 15 of these still available articles (10.7%) present no evident watermark clearly indicating the presence of a retraction (Acharya & Mandal, ; Asgary & Eghbal, ; Cuoghi, Sella, & de Mendonça, ; Dionysopoulos, Koliniotou‐Koumpia, Helvatzoglou‐Antoniades, & Kotsanos, ; Ellakwa & El‐Sheikh, ; Gulsahi et al, ; Khattab, El‐Seify, Shaaban, Radojevic, & Jankovic, ; Kurtulmus & Cotert, ; Nayyar, Khan, Bafna, Ahmed, & Chaluvaiah, ; Ni, Lin, Liu, & Xiao, ; Palenik, ; Scotti, Cardelli, Baldissara, & Monaco, ; Sumanth et al, ; Wang et al, ). The abstracts of 157 out of 180 retracted publications (87.2%) are still available on Pubmed, but 8 of these (5.1%) present neither a footnote nor any clear indication of the presence of a retraction notice (Agrawal, Singh, Rashmikant, Singh, & Chand, ; Dumitrescu, Zetu, & Teslaru, ; Ehrlich et al, ; Kumar et al, ; Maté Sánchez de Val et al, ; Rabanal, Bral, & Goldstein, ; Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Ketamine is an N-methyl-d-aspartate (NMDA) receptor antagonist that produces a state of sedation, anaesthesia, immobility, analgesia, and amnesia. 7,8 Sedative premedication in children is commonly administered via the oral, rectal, sublingual, and intranasal routes with varying degrees of patient acceptance. 1e8 Inhalation of nebulised drug is an alternative method of administration that is relatively easy to set up, does not require venepuncture, and is associated with high bioavailability of the administered drug.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…They also reported incidence of severe agitation of 7.1% in group K (on postoperative day 1) whereas no incidence of severe agitation was noted in group KM similar to our study. Similarly, Ahmed M. Khattab, Zeinab A., El-Seify, et al 32 reported an agitation incidence of 37% in group M and 10.9% in group KM. Their use of Ketamine and Midazolam as oral premedication may suggest altered and possibly inconsistent pharmacokinetics and dynamics compared to IV use of the same drugs.…”
Section: Gulcan Erk Dilsenmentioning
confidence: 81%